Risk Identification Strategies and Supply Chain Resilience: A Case Study of Soroti Fruits Limited Teju Juice Company - Isaac Igulot (Uganda Christian University, 2025)
Supply chain resilience is increasingly acknowledged as an essential element for organizations to effectively manage disruptions, sustain operational continuity and preserve competitive advantage. The initial step in developing a resilient supply chain is effective identification of risks. This research examines a variety of strategies for detecting risk within the supply chain, highlighting both conventional and innovative methodologies. Conventional techniques involve risk assessment, analysis of historical data and supplier evaluations. While newer on data analytics, artificial intelligence and real time monitoring technologies. The research also investigates the importance of collaboration and communication in the risk identification process, emphasizing cross functional teams and external partners can enhance a more thorough risk management framework. Furthermore, it continues to discuss the link between risk identification supply and supply chain resilience suggesting that early detection of potential risks allows organizations to put in place timely mitigation strategies. Basically, the study advocates for a combined approach to risk identification that merges various strategies to ensure the supply chain’s strength against a number of disruptions ranging from natural disasters to geopolitical issues and economic changes. This study seeks to represent a comprehensive examination of contemporary risks identification methodologies with the objective of explaining how organizations can strengthen their resilience, ensure operational continuity and promote enduring sustainability amid progressively unstable conditions.